Psychological Analysis on Autogenesis as Preface to God Cognition (A Comparative Analysis of View Point of Imam Ali ibn Abu Talib --peace be upon him-and Scholars of Education and Pedagogy) - Seyed Eshaq Hoseini Kuhsari; Ali Redha Mohammad Redhaei (International Journal of Nusantara Islam, 2014)
One of the questions which has engaged the mind and soul of many people is: how can fifteen century old teachings of Islam and its guide lines given by Prophet Mohammad (peace be upon him) and infallible Imams (peace be upon them) can answer the needs of today and how can it lead the way of today’s people to perfection? Is the teaching of Islam compatible with science of today?The present papertries to emphasize on teachings of Islam not belonging to people of specific time period, and have static and variable laws and comprehensive view on every aspect of life. It also performs an analytic and comparative study on viewpoint of psychologists and sayings of Imam Ali's concerning the most fundamental need of humanity; Autogenesis and perfectionism. Probably it may help us answer the above questions and will also help us in manifesting some part of that infallible Imam's endless knowledge.